2006
DOI: 10.1159/000093474
|View full text |Cite
|
Sign up to set email alerts
|

Combined Biodifferentiating and Antiangiogenic Oral Metronomic Therapy is Feasible and Effective in Relapsed Solid Tumors in Children: Single-Center Pilot Study

Abstract: To outline an outpatient-based treatment for children with relapsed solid tumors, who already have been extensively pretreated, we defined a 4-drug protocol named COMBAT (combined oral maintenance biodifferentiating and antiangiogenic therapy). Using this protocol, we performed a pilot study to determine its feasibility in children with relapsed and/or high-risk pediatric solid tumors. Patients and Methods: 22 children received the COMBAT protocol. Treatment consisted of daily celecoxib administration along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 40 publications
(44 reference statements)
3
63
1
Order By: Relevance
“…The novelty of our study combines metronomic chemotherapy with an anti-angiogenic agent in the clinical setting. There are few published clinical trials using such a combination, mostly phase I-II or abstracts [32][33][34][35][36][37][38][39]. In contrast to our study which showed benefit of docetaxel with thalidomide in solid tumors, Colleoni found that the addition of thalidomide to metronomic chemotherapy in advanced breast cancer patients did not improve the response rate compared to chemotherapy alone [40].…”
Section: Discussioncontrasting
confidence: 94%
“…The novelty of our study combines metronomic chemotherapy with an anti-angiogenic agent in the clinical setting. There are few published clinical trials using such a combination, mostly phase I-II or abstracts [32][33][34][35][36][37][38][39]. In contrast to our study which showed benefit of docetaxel with thalidomide in solid tumors, Colleoni found that the addition of thalidomide to metronomic chemotherapy in advanced breast cancer patients did not improve the response rate compared to chemotherapy alone [40].…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, the greater sensitivity of endothelial cells in comparison to tumor cells allows for significantly lower doses of the drug to be effective, thus improving tolerability (5,6). anti-angiogenic chemotherapy has entered clinical trials for various vascular tumors refractory to conventional chemotherapy (4,(7)(8)(9). in our study, 40% of children with recurrent or progressive cancer, treated with daily low-dose oral etoposide alternating every 21 days with daily low-dose oral cyclophosphamide combined with daily oral thalidomide and celecoxib, exhibited a prolonged or persistent progression-free disease status (7).…”
Section: Introductionmentioning
confidence: 80%
“…We recently incorporated etoposide as part of a four-drug anti-angiogenic chemotherapy regimen (thalidomide, celecoxib, etoposide and cyclophosphamide), which showed prolonged disease-free status in pediatric patients with recurrent or progressive cancer (7). Similarly, etoposide was part of a four-drug regimen named cOmBat (combined oral maintenance biodifferentiating and anti-angiogenic therapy), which was effective in solid tumors in children which had relapsed (9). this regimen included celecoxib, cis-retinoic acid, metronomic temozolomide and low-dose etoposide.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and toxicity of the combat regimens were recently reported 4,9 , and so here we focus on vinblastine, which was the most successful part of our patient's treatment. Vinblastine belongs to the group of vinca alkaloids derived from leaf extracts of the periwinkle plant 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Because of grade 4 myelosuppression lasting 5 weeks and the reappearance of clinical symptoms, that treatment protocol was stopped. The patient was then offered low-dose combat metronomic chemotherapy (temozolomide, etoposide, celecoxib, retinoic acid) 4 , which contained combat ii (plus vitamin D and fenofibrate) and combat iii 5 (plus bevacizumab) for 31 months, using temozolomide 30 mg/m 2 daily for 42 days and etoposide 25 mg/m 2 daily. However, that dosing schedule had to be reduced by 50% because of grades 3 and 4 bone marrow toxicity.…”
Section: Case Descriptionmentioning
confidence: 99%